Subcutaneous transplantation of human embryonic stem cells-derived pituitary organoids - Sasaki, Hiroo; Suga, Hidetaka; Takeuchi, Kazuhito; Nagata, Yuichi; Harada, Hideyuki; Kondo, Tatsuma; Ito, Eiji; Maeda, Sachi; Sakakibara, Mayu; Soen, Mika; Miwata, Tsutomu; Asano, Tomoyoshi; et al. (Frontiers in Endocrinology, 2023)
Introduction: The pituitary gland, regulating various hormones, is central in the endocrine system. As spontaneous recovery from hypopituitarism is rare, and exogenous-hormone substitution is clumsy, pituitary replacement via regenerative medicine, using pluripotent stem cells, is desirable. We have developed a differentiation method that in mice yields pituitary organoids (POs) derived from human embryonic stem cells (hESC). Efficacy of these POs, transplanted subcutaneously into hypopituitary mice, in reversing hypopituitarism was studied. Methods: hESC-derived POs were transplanted into inguinal subcutaneous white adipose tissue (ISWAT) and beneath dorsal skin, a relatively avascular region (AR), of hypophysectomized severe combined immunodeficient (SCID) mice. Pituitary function was evaluated thereafter for < 6mo, assaying basal plasma ACTH and ACTH response to corticotropin-releasing hormone (CRH) stimulation. Histopathologic examination of organoids 150d after transplantation assessed engraftment. Some mice received an inhibitor of vascular endothelial growth factor (VEGF) to permit assessment of how angiogenesis contributed to subcutaneous engraftment. Results: During follow-up, both basal and CRH-stimulated plasma ACTH levels were significantly higher in the ISWAT group (p < 0.001 – 0.05 and 0.001 – 0.005, respectively) than in a sham-operated group. ACTH secretion also was higher in the ISWAT group than in the AR group. Histopathologic study found ACTH-producing human pituitary-cell clusters in both groups of allografts, which had acquired a microvasculature. POs qPCR showed expression of angiogenetic factors. Plasma ACTH levels decreased with VEGF-inhibitor administration. Conclusions: Subcutaneous transplantation of hESC-derived POs into hypopituitary SCID mice efficaciously renders recipients ACTH-sufficient.